GAMBARAN KESEHATAN MENTAL REMAJA SMPN 2 BANGKINANG KOTA KABUPATEN KAMPAR - ALINI ALINI; LANGEN NIDHANA MEISYALLA (Jurnal Ners, 2022)
Adolescence is a critical period in a person's development cycle. Data on adolescent mental health in Indonesia alone in 2018, there were 9.8% of the prevalence of mental emotional disorders with symptoms of depression and anxiety for adolescents aged > 15 years, an increase compared to 2013. This study aims to determine the mental health picture of adolescents at SMPN 2 Bangkinang Kampar Regency City. This study uses a quantitative non-experimental research approach with a scale as a measuring tool. The design used in this research is descriptive analysis. The population in this study were all students in grades VII - IX at SMPN 2 Bangkinang Kota, totaling 576 people with a total sample of 282 people. This study uses a total sampling technique. The data collection tool used a Mental Health Continuum-ShortForm (MHC-SF) questionnaire. Data analysis used univariate analysis. The results showed that most of the respondents had high emotional well-being as many as 217 people (96.0%), most of the respondents had high social welfare as many as 221 people (78.4%), and most of the respondents had high psychological well-being as many as 243 people (86.2 people). %). It is hoped that the results of this study can be the basis for developing preventive and promotive programs on adolescent mental health involving the participation of family, school, peers so that adolescents are able to have good protective factors and be able to cope with problems that occur adaptively.